2022
DOI: 10.3390/f13040586
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Salt Stress via Habitat-Adapted Symbiosis

Abstract: Halotolerant plant-growth-promoting rhizobacteria (PGPR) could not only promote plant growth, but also help in counteracting the detrimental effects of salt stress. In the present study, a total of 76 bacteria were isolated from the rhizosphere, non-rhizospheric soil and endophytes of the halophyte Salsola tetrandra, collected from natural saline soils in Algeria. Phylogenetic analysis based on the 16S rDNA sequence of Gram-negative bacteria (n = 51) identified, showed seventeen representative isolates grouped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Although these studies showed that PGPR promote proline accumulation, other studies found that PGPR reduce proline accumulation [64,161,167,176,209]. These discrepancies can be attributed to the different mechanism of PGPR to combat drought, changes in bacterial species, bacterial communication mechanisms with plants, bacterial interaction, and severity of drought stress.…”
Section: Osmotic Adjustment Through the Synthesis And Accumulation Of...mentioning
confidence: 94%
“…Although these studies showed that PGPR promote proline accumulation, other studies found that PGPR reduce proline accumulation [64,161,167,176,209]. These discrepancies can be attributed to the different mechanism of PGPR to combat drought, changes in bacterial species, bacterial communication mechanisms with plants, bacterial interaction, and severity of drought stress.…”
Section: Osmotic Adjustment Through the Synthesis And Accumulation Of...mentioning
confidence: 94%
“…Plant growth-promoting bacteria (PGPB) are the target of intensive research studies into their efficient use as biofertilizers, biocontrol agents, and bioremediation agents, as well as numerous other applications [45]. There are examples of bacteria (Acinetobacter, Enterobacter, Providencia, and Pseudomonas) that help survive temperature changes, acidification, and mineral salt uptake [46]. We suspect that Bacillus spp.…”
Section: Relationships Between Soil Fertility and The Role Of Bacteri...mentioning
confidence: 99%
“…Despite the existence of all these potentialities, the capacity for root colonization and competition for space and nutrients remain the critical points of BCA competence. These properties can be examined in vivo by inoculation into a workable gnotobiotic system on model plants or on the target plant under controlled conditions [120,121]. In this case, the interaction of the BCA of the plant and the pathogen are the only parameters to be controlled.…”
Section: In Situ Bca Responsesmentioning
confidence: 99%